Using the Defensive Style Questionnaire to evaluate the impact of sex reassignment surgery on defensive mechanisms in transsexual patients - Lobato,Maria Inês (2009)
Objective: To evaluate the impact of sex reassignment surgery on the defense mechanisms of 32 transsexual patients at two different points in time using the Defensive Style Questionnaire. Method: The Defensive Style Questionnaire was applied to 32 patients upon their admission to the Gender Identity Disorder Program, and 12 months after they had undergone sex reassignment surgery. Results: There were changes in two defense mechanisms: anticipation and idealization. However, no significant differences were observed in terms of the mature, neurotic and immature categories. Discussion: One possible explanation for this result is the fact that the procedure does not resolve gender dysphoria, which is a core symptom in such patients. Another aspect is related to the early onset of the gender identity disorder, which determines a more regressive defensive structure in these patients. Conclusion: Sex reassignment surgery did not improve the defensive profile as measured by the Defensive Style Questionnaire.